Studying the effect of teichoic acid extracted from the wall of Staphylococcus aureus isolated from cases of osteomyelitis on its pathogenesis (Journal of the College of Basic Education, 2023)
The study included isolation and identification of Staphylococcus aureus from cases of osteomyelitis, and then extraction of teichoic acid from the wall of Staphylococcus aureus bacteria, and an attempt to investigate teichoic acid antibodies in the blood serum of patients with osteomyelitis.Thirty-four samples (pus and blood) were collected from patients with osteomyelitis hospitalized in Baquba General Hospital- Diyala Health Department.The results of aerobic bacterial culture of pus samples were 22 positive and 12 negative. The results of bacterial culture and biochemical tests showed the presence of 9 isolates of Staphylococcus aureus. The extraction and partial purification of teichoic acid from the wall of Staphylococcus aureus bacteria was carried out using the mechanical disintegration process using the rapid shaking method to break the cell wall of Staphylococcus aureus by adding glass beads and obtaining an appropriate amount of broken cells and then partial extraction and purification of the wall The broken down based on enzymatic digestion by proteolytic enzyme as well as the use of sodium dodecyl sulphate (SDS) compound to remove the cytoplasmic membranes. As well as the investigation of teichoic acid antibodies extracted from the wall of Staphylococcus aureus in the blood serum of patients with osteoarthritis And pure, based on the gel immunodiffusion test, with the appearance of a single sedimentary band.